Development and Initial Testing of a Modified UroVysion-Based Fluorescence In Situ Hybridization Score for Prediction of Progression in Bladder Cancer. Issue 2 (16th November 2019) - Kocsmár, Ildikó; Pajor, Gábor; Gyöngyösi, Benedek; Székely, Eszter; Varga, Márton; Kocsmár, Éva; Kenessey, István; Beöthe, Tamás; Süle, Norbert; Majoros, Attila; Szendrői, Attila; Nyírády, Péter; et al.
Abstract: Objectives: Our aim was to predict progression of non-muscle-invasive bladder urothelial carcinomas (NMIUCs) into muscle-invasive disease by assessing cytogenetic abnormality of tumors with a new UroVysion scoring system. Methods: Seventy-five bladder cancer cases (including 57 NMIUCs) were classified according to the quantitatively assessed degree of UroVysion-detected chromosomal abnormalities into urine fluorescence in situ hybridization score (UFS) groups: UFS I, II, and III. Cox time-to-event, Kaplan-Meier, and C-statistics analyses were performed. Results: UFS proved to be an independent prognostic factor of progression-free survival (PFS) and time to progression (TTP). NMIUCs with UFS III had a 34.05-fold increased hazard for progression to muscle-invasive cancer (TTP; 95% confidence interval, 5.841-198.5; P < .001) in comparison with UFS I to II cases. The addition of UFS to conventional risk scores increased the C-index for PFS and TTP. Conclusions: UFS can indicate an increased risk for progression into muscle-invasive disease in patients with NMIUC and improves prognostic accuracy of the current clinical risk assessment systems.